1996
DOI: 10.1016/s0736-5748(96)00045-7
|View full text |Cite
|
Sign up to set email alerts
|

Activity blockade does not prevent the construction of olfactory glomeruli in the mothManduca sexta

Abstract: During metamorphic development, the arrival at the olfactory (antennal) lobe of olfactory receptor axons initiates the process of glomerulus formation. The glomeruli are discrete spheroidal regions of neuropil that are the sites of synaptic interactions among receptor neurons and their target antennal-lobe neurons. The process of glomerulus formation begins as groups of receptor axons form protoglomeruli. These dense clusters of terminal branches mostly are discrete entities from the time they can be recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…1 (C,D)] . Even as they begin to form, the protoglomeruli each occupy an almost discrete territory with little overlap of laterally extending axonal branches (Oland et al, 1996b). Within a stage, however, the individual protoglomeruli become Distinguishing processes as axonal or dendritic is even less straightforward in the invertebrates than it is in the vertebrates.…”
Section: Development Of Receptor Axonsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (C,D)] . Even as they begin to form, the protoglomeruli each occupy an almost discrete territory with little overlap of laterally extending axonal branches (Oland et al, 1996b). Within a stage, however, the individual protoglomeruli become Distinguishing processes as axonal or dendritic is even less straightforward in the invertebrates than it is in the vertebrates.…”
Section: Development Of Receptor Axonsmentioning
confidence: 99%
“…In the moth, odorant-induced activity in the receptor neurons first appears only in the last few days of metamorphic development, long after glomeruli develop (Schweitzer et al, 1976); and intracellular recordings from multiglomerular neurons revealed no responses to electrical stimulation of the antennal nerve prior to stage 9 (Tolbert et al, 1983). However, some of the receptor axons and some of the antennal-lobe neurons are spontaneously active during the critical stages of glomerulus formation (Oland et al, 1996b; H. G. Marrero and L. A. Oland, unpub.…”
Section: Elimination Of Na-dependent Activitymentioning
confidence: 99%
“…The dogma has long been that invertebrate circuits are hard-wired from the early stages of development, and do not employ activity-dependent refinement in a manner comparable to vertebrates. Indeed, a strong body of experimental evidence supports this position, in both primary sensory circuits and higher order systems (Berdnik et al, 2006; Hiesinger et al, 2006; Jefferis et al, 2004; Oland et al, 1996; Scott et al, 2003; Srahna et al, 2006). However, both classical and recent evidence has shown that environmental experience in invertebrates is capable of modulating the connectivity of sensory and higher order circuits (Chiba et al, 1988; Devaud et al, 2001, 2003; Fahrbach et al, 1995; Sachse et al, 2007; Withers et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Developing neurons in primary olfactory centers [antennal lobes (ALs)] of the brain of the sphinx moth, Manduca sexta, show bursts of electrical activity (Mercer and Hildebrand 2002a;Oland et al 1996). Here, we examine intrinsic properties that contribute to the characteristic form of electrical activity apparent in these developing neurons: their ability to generate prolonged membrane depolarizations or plateau potentials.…”
Section: Introductionmentioning
confidence: 99%
“…During metamorphosis, including critical stages of glomerulus formation, electrical activity can be detected in antennal nerve (sensory afferent) fibers and in AL neurons of the moth (Mercer and Hildebrand 2002a;Oland et al 1996). In AL neurons, this activity is characterized by prolonged membrane depolarizations that resemble plateau potentials (Mercer and Hildebrand 2002a).…”
Section: Introductionmentioning
confidence: 99%